Gastroesophageal reflux disease with Thal fundoplication - Irwan Effendi; Yusri Dianne Jurnalis; Yorva Sayoeti; Yusirwan Yusuf (Indonesian Pediatric Society, 2010)
Gastroesophageal reflux (GER) is a common phenomenon among heathy infants, with approximately 50% of infants aged 0 to 3 months and 67% of infants aged 4 months experiencing at least one episode of vomiting per day. GER defined as regurgitation of gastric contents into the esophagus or mouth. GER typically improves through the first postnatal year, with only 5% of healthy 12 month old infants experiencing vomiting.1,2 Complicated GER or gastroesophageal reflux disease (GERD) has been reported to affect up to 8% of infants and children with GER.l,3 Antireflux procedures (ARPs) are increasingly offered to control GERD symptoms. We report a case of a baby with GERD and treated with ThaI fundoplication procedures. Fundoplication procedure is rarely performed in management of GERD, and this is the first fundoplication procedure in children with GERD at M. Djamil Hospital.